The role of guidance and counseling service in helping students with academic stress - Daulay, Nurussakinah; Harahap, Ade Chita Putri; Sinaga, M. Harwansyah Putra (ProGCouns: Journal of Professionals in Guidance and Counseling, 2022)
This paper aims to urge the role of guidance and counseling services in helping students with academic stress in Indonesia. This article is a literature review, so the type of data used by the author in this article is data obtained from a literature study by looking for theoretical references that are relevant to the issues. There are 21 studies that have discussed that academic stress can be minimized with the help of counseling services. Several literature have shown that five out of nine guidance and counseling services have been shown to contribute positively to academic stress, such as: 1) information services using stress management techniques; 2) group guidance services using mind mapping techniques, problem solving methods, rational emotive behavior therapy approaches; discussion techniques; self-instruction techniques; 3) individual counseling services; 4) group counseling services; 5) orientation service. The findings provide an empirical foundation regarding the importance of evidence-based practices on guidance and counseling services in reducing students’ academic stress symptoms both physically and psychologically. Moreover, students can achieve psychological well-being.